Pengaruh Harga dan Customer Review Terhadap Minat Beli Produk Mascara Maybelline pada Pengguna Shopee Mall Indonesia - Putri Ayu Agustien; Donant Alananto Iskandar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study describes the effect of price and customer reviews on the purchase intention of Maybelline mascara products among Shopee Mall Indonesia users in Jakarta. This study uses a quantitative method by distributing questionnaires with Google formto 152 respondents which is then processed using the SPSS version 13.0 program using a saturated sampling technique to take sample data. The results of the hypothesis test (ttest) thatthe price does not have a positive effect on buying interest with a t count value of 1.558 <ttable of 1.976. the results of the hypothesis test (ttest) thatcustomer reviews have a positive effect on buying interest with a t-count value of 9.425 > t-table 1.976.